A bi-objective optimisation approach for the critical chain project scheduling problem. (14th September 2021) - Peng, Wuliang; Lin, Jiali; Ma, Xueli
Since time and cost are two important issues in real-life project scheduling applications, the optimisation problems about project make-span and cost have been extensively studied over the last few decades. This study addresses the bi-objective critical chain project scheduling problem aiming at minimising both project make-span and cost. We formulate the conceptual model considering project make-span and cost under both the resource-constraints and precedence relations. In the model, the promised delivery time is used as project make-span, and the discounted cost is used to measure project cost. To solve the problem, an evolutionary algorithm based on greedy randomised adaptive search procedure (GRASP) is proposed to search for the non-dominated solutions of the problem. Several neighbourhood search methods are investigated and compared with each other regarding four multi-objective performance measures: optimal ratio, hyper-volume indicator, epsilon metric and average distance. The computational tests have indicated the algorithm with variable neighbourhood appears to be superior to others.